Job Demands, Job Resources dan Kemampuan Adaptasi Karir terhadap Niat Mengundurkan Diri - Hendra Kusuma; Siti Zahreni; Hasnida Hasnida (JURNAL ILMIAH MANAJEMEN & BISNIS, 2019)
This study aims to see the effect of job demands, job resources and career adaptability on turnover intention among palm oil field assistant. Employee needs to balance demands (eg. job overload) and resources, in order to reduce stress and turnover intention. Resources can be divided into job resources (eg. job security, organization support, growth opportunities and advancement) and personal resources (eg. career adaptability). This study used structural equation modeling (SEM) with AMOS. Result indicates positive influence of job demands and negative influence of both job resources and career adaptability on turnover intention. However, career adaptability also show mediating effect in the relationship between job demands and job resources with turnover intention.